The influence of individual determinants in the delay of the tuberculosis diagnosis - Trigueiro,Débora Raquel Soares Guedes (2014)
Analyzes the influence of individual determinants on the service usage pattern to define the time it takes for tuberculosis patients to seek care in order to discover their diagnosis. Cross-sectional research undertaken in a Northeastern capital of Brazil, involving 101 patients. The variables were submitted to statistical treatment through median and Mann-Whitney and Kruskal-Wallis non-parametric tests. A median 20 days was estimated for the patients' general delay, showing that single individuals who had less than eight years of study and were unemployed were the ones who delayed most in seeking a health service (30 days). The theoretic model used confirmed the presence of predisposing factors that favor the inequalities in the search for and obtainment of care. The inclusion of the subjective dimension in the guarantee of integral care can contribute to the renewal of practices and reduction of iniquities for individuals affected by tuberculosis.